Nutrition and metabolism in sports, exercise, and health - Kang, Jie (Routledge, Taylor & Francis Group, 2018)
The second edition of Nutrition and Metabolism in Sports, Exercise and Health offers a clear and comprehensive introduction to sport and exercise nutrition, integrating key nutritional facts, concepts and dietary guidelines with a thorough discussion of the fundamental biological science underpinning physiological and metabolic processes. As such, Nutrition and Metabolism in Sports, Exercise and Health is essential reading for all students of sport and exercise science, kinesiology, physical therapy, strength and conditioning, nutrition or health sciences.